2021
DOI: 10.3390/rs13234880
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Subtidal and Intertidal Seagrass Meadows via Application of the Feature Pyramid Network to Unmanned Aerial Vehicle Orthophotos

Abstract: Seagrass meadows are one of the blue carbon ecosystems that continue to decline worldwide. Frequent mapping is essential to monitor seagrass meadows for understanding change processes including seasonal variations and influences of meteorological and oceanic events such as typhoons and cyclones. Such mapping approaches may also enhance seagrass blue carbon strategy and management practices. Although unmanned aerial vehicle (UAV) aerial photography has been widely conducted for this purpose, there have been cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…For example, satellite images (in addition to low accuracy) are often restricted by cloud cover, high tides, and low temporal resolution. On the other hand, drone operation can be hampered by strong winds, rain, higher operational costs, relatively short flight durations, privacy concerns, and airspace restrictions (e.g., around airports, marine mammals, reserves) (Chen & Sasaki, 2021; Nababan et al, 2021). Nevertheless, using drones as a monitoring tool is flexible because the flying altitude (and hence spatial extents and grain) is under direct user control, and it allows for easy sampling of difficult‐to‐reach areas like across channels and deep soft mud.…”
Section: Discussionmentioning
confidence: 99%
“…For example, satellite images (in addition to low accuracy) are often restricted by cloud cover, high tides, and low temporal resolution. On the other hand, drone operation can be hampered by strong winds, rain, higher operational costs, relatively short flight durations, privacy concerns, and airspace restrictions (e.g., around airports, marine mammals, reserves) (Chen & Sasaki, 2021; Nababan et al, 2021). Nevertheless, using drones as a monitoring tool is flexible because the flying altitude (and hence spatial extents and grain) is under direct user control, and it allows for easy sampling of difficult‐to‐reach areas like across channels and deep soft mud.…”
Section: Discussionmentioning
confidence: 99%
“…To minimize the potential for misinterpretation, which is occasionally encountered in the conventional manual annotation of multiple LULC classes, we initially applied the ISODATA approach to the QGIS acquired on 12 February 2023, which was not used for model training [25,35]. Based on 224 Field GPS points and very high-resolution Google Earth and Planet Scope Dove images, the ISODATA output image was manually corrected using a raster editor tool in QGIS (QGIS Development Team (2009); Open-Source Geospatial Foundation Project, http://qgis.osgeo.org, accessed on 10 June 2023).…”
Section: Ground Truth Data Collection and Creating A Labeled Imagementioning
confidence: 99%
“…Numerous studies have demonstrated the superior performance of deep learning models over traditional ML methods in remote sensing applications [22][23][24]. Among state-of-the-art models, the U-Net segmentation model and artificial neural networks (ANNs) have consistently demonstrated superior performance in remote sensing image analysis [25][26][27]. However, limited studies have applied the U-Net and ANN models using different spatial resolution of satellite images for mangrove ecosystem [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…UAVs have been used to map seagrass and proximal habitats using a variety of techniques underpinned by differing statistical methods. For example, Ventura et al, 2016 [35], and Chen and Sasaki, 2021 [36], used a pixel-based approach whereby each individual photographic pixel is assigned a value or classification representing a habitat type. Alternatively, Ventura et al, 2016 [35], Ventura et al, 2018 [37], Duffy et al, 2018 [33], Nahirnick et al, 2018 [38], Ellis et al, 2020 [39], and Papakonstantinou et al, 2020 [40], used an object-based image analysis (OBIA) approach in which pixels are spatially grouped together in segments based on the similarity of their properties and classified.…”
Section: Introductionmentioning
confidence: 99%